2016
DOI: 10.1128/cvi.00462-15
|View full text |Cite
|
Sign up to set email alerts
|

Display of Antigens on Polyester Inclusions Lowers the Antigen Concentration Required for a Bovine Tuberculosis Skin Test

Abstract: eThe tuberculin skin test is the primary screening test for the diagnosis of bovine tuberculosis (TB), and use of this test has been very valuable in the control of this disease in many countries. However, the test lacks specificity when cattle have been exposed to environmental mycobacteria or vaccinated with Mycobacterium bovis bacille Calmette-Guérin (BCG). Recent studies showed that the use of three or four recombinant mycobacterial proteins, including 6-kDa early secretory antigenic target (ESAT6), 10-kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…This study evaluated the potential application of selfassembled polyester particles produced in E. coli cells as a carrier system for the delivery of mycobacterial antigens H4 and H28. A number of studies have shown that polyester particles could be genetically engineered to display antigens of interest (29,30,37). This particle-based vaccine delivery system had been shown to enhance antigen-specific immune responses (25,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the potential application of selfassembled polyester particles produced in E. coli cells as a carrier system for the delivery of mycobacterial antigens H4 and H28. A number of studies have shown that polyester particles could be genetically engineered to display antigens of interest (29,30,37). This particle-based vaccine delivery system had been shown to enhance antigen-specific immune responses (25,38).…”
Section: Discussionmentioning
confidence: 99%
“…This concept of using biopolyester particles for vaccine delivery is further underpinned by their unique favorable properties such as biocompatibility with mammalian systems (23)(24)(25)(26)(27)(28). Hepatitis C and TB antigens displayed on the particle surface have demonstrated increased immunogenicity when compared with their soluble forms, suggesting that polyester particles are capable of increasing the immunogenicity of vaccines when desired antigen candidates are displayed on their surfaces (29)(30)(31). In addition, polyester particles could serve as a depot for prolonged multivalent-antigen display to provide enhanced immunogenicity.…”
mentioning
confidence: 99%
“…It is essential that any given nanoparticle intended for human therapeutic applications such as drug delivery does not elicit any kind of immunological noise. In a case study by Parlane and colleagues [72], however, the use of engineered PHAs granules was shown to increase pro-inflammatory cytokine levels for unknown reasons. In the case of exosomes, it has been suggested that care should be taken regarding the choice of exosomes [40].…”
Section: Immunological Response Of Bnps -A Major Setback?mentioning
confidence: 97%
“…A further extension of these findings is the use of granules for the effective detection of M. tuberculosis and Mycobacterium bovis in infected and non-infected animals. To distinguish infected from non-infected animals, multiple tuberculosis antigens including ESAT6, 10-kDa culture filtrate protein (CFP10), Rv3615c, and Rv3020c were fused to the PHA synthase protein and were displayed on the granules[72]. These granules served as a highly sensitive system for the identification of M. bovis-infected animals from skin tests and furthermore allowed for the discrimination between naturally M. bovis-infected cattle from BCG-vaccinated non-infected animals.A fusion protein of B7-2, a costimulatory molecule, fused to PhaP1 was expressed and displayed on granules in recombinant E. coli.…”
mentioning
confidence: 99%
“…*Kinetic parameters are not mentioned in the reference. Hay et al, 2015;Parlane et al, 2016a). Assembly of immobilized multiprotein complexes enables multi-enzymatic cascade systems with superior catalytic performance as recently reviewed (Hwang and Lee, 2019).…”
Section: Magnetosome Membrane Protein Mms13mentioning
confidence: 99%